Transport Phenomena on Single Walled Carbon Nanotubes - KAZEMZADEH, A.; VALIZADEH, M.; RAISIAN, H. (Asian Journal of Chemistry, 2010)
One of the most fascinating properties of carbon nanotubes is the predicted interplay between geometrical and electronic structure. The topics include a giant Aharonov-Bohm effect on the band gap and landau-level formation and Hall effect in magnetic fields. Individual large diameter (8 to 15 nm) semi conducting single-walled carbon nanotube is found to exhibit are bipolar field-effect transistor behaviour. The effect of temperature and ultraviolet radiation on their electrical properties is elucidated. We also discuss recent development in contacting nanotubes, which should soon allow study of their intrinsic transport properties. In this research electrical properties and transport phenomena on single-walled carbon nanotubes have studied with measurement of Raman spectroscopy, XRD, ESR, I -V curve, C-V hardness and band gap methods in the UV-Vis area and suitable results obtain from analyses device in the field of electron transport phenomena in carbon nanotubes.